Beyond adjustment: the Asian experience - "Streeten, Paul (ed.)" (Washington, 1988)
This book, edited by Paul Streeten, examines the ends and means of adjustment, aspects of trade policy, and lessons from the experience of South and East Asia, as well as comparing the debt situations of Asian and Latin American countries.
Keywords: Asia - Economic policy - Congresses